Modeling the impact of emission credit systems on automotive product portfolios: A mathematical analysis of policy effects in Europe, China, and the U.S. under different demand scenarios - Zewei Shi (Junior Management Science (JUMS), 2025)
In the midst of the global climate crisis, governments worldwide have implemented a range of emission policies aimed at en-couraging more production of the environmentally friendly vehicle. However, the exact impact of these policies on automakers'production portfolios and profitability remains uncertain and challenging to anticipate. This paper presents a comprehensiveanalysis of three major emission regulation policies enacted by the European Union (EU), China, and the United States (U.S.),evaluating their influence on car manufacturers. Leveraging a mathematical model, this paper adopt the perspective of in-dividual manufacturers seeking to maximize revenue, delving into the intricacies of these policies. Furthermore, this articleconduct sensitivity and factorial analyses to assess the impact of policy parameters. The findings reveal that all three majoremission policies contribute to an increase in the production of low-emission vehicles. However, China's policy has the leastimpact on manufacturers' profits and relies more on market demand to reduce the average carbon fleet emissions comparedto the policies in the EU and the U.S. In conclusion, this paper underscores that different policy systems yield varying profitoutcomes for manufacturers, necessitating adjustments to production portfolios for sustained profitability and the significanceof mathematical models in aiding manufacturers' understanding of evolving policies and making informed predictions in adynamic regulatory landscape.
Keywords: 650; automotive production; green transition; international emission policies; regulatory impact; sustainability